The hunt for migratory signifiers. - Turkina, Olesya; Mazin, Victor (Third Text, 2003)
In the final decades of the twentieth century, the rapid consolidation of the visual environment of human beings is witnessed. It continues to be demarcated by an endless succession of new signs. The oversaturated environment is in a state of constant resignification. The special characteristics of the perception of images have to do, not only with the constant stimulation of the visual apparatus, but with a kind of split between the unconscious absorption of information and its analytical processing. A very special role in this rapidly self reproducing environment belongs to modern visual art which functions as a marginal testing ground for innovative experiments, as a zone of critical response and thus, apparently, a forecasting zone. Art displays the symptoms of the future evolution of the environment. In the sphere of visual art, the powerful regressive discourse continues to build on the dichotomies of real and mass art, art by geniuses and art by charlatans, "authentic" and "secondary" art, "empty" and "meaningful" art.